Is there a relationship between morphokinetic parameters and obstetrical complications? An analysis of singleton live births after single fresh embryo transfer - Avital Wertheimer; Onit Sapir; Alyssa Hochberg; Avi Ben-Haroush; Eran Altman; Tzippy Shochat; Eran Hadar; Yoel Shufaro (BMC, 2024)
Abstract Background With the advancement in embryology and the introduction of time-lapse monitoring system, the embryologists' goal might be to find not only the embryo with the highest probability of live birth, but also the embryo with the highest probability to progress to a healthy full-term delivery. Thus, we aimed to investigate the association between morphokinetic time-lapse parameters and obstetrical and perinatal complications. Methods A cohort study reviewing fertility and delivery files of all singletone births from IVF patients whose embryos were cultured in a time-lapse monitoring system and had a single fresh embryo transfer at our center between 2013-2019. We conducted multiple comparisons between complicated and uncomplicated pregnancies of each perinatal complication, including: gestational diabetes mellitus (GDM); small for gestational age (SGA); pre-eclamptic toxemia (PET); preterm labor < 37 weeks of gestation (PTL); and third stage of labor complications. A comparison between pregnancies with and without a composite outcome of placental complications including GDM, SGA, PET and PTL was also conducted. Baseline characteristics, treatment and morphokinetic parameters in complicated and uncomplicated gestations were compared. Logistic regression analysis was utilized to adjust results for potential confounders. Results One hundred seventy-six single embryo transfers resulted in 176 live births. Morphokinetic time-lapse parameters were similar between the groups, except for a shorter time to full blastulation in the SGA group (tB-tPNf = 75.5 ± 1.3 h vs. 79.5 ± 4.8 in the non-SGA group, p < 0.001), and shorter third cell cycle duration in the PET group (CC3 = 12.4 ± 1.1 h vs. 13.6 ± 2.9 in the non-PET group, p = 0.02). On multivariate regression analysis, none of the morphokinetic parameters were found to be significantly correlated with any of the perinatal complications. Conclusion Time-lapse morphokinetic parameters of the embryo transferred are not associated with adverse obstetric and perinatal outcomes.